Future changes in the supply of goods and services from natural ecosystems: prospects for the European north - Jansson, Roland; Nilsson, Christer; Keskitalo, E. Carina H.; Vlasova, Tatiana; Sutinen, Marja-Liisa; Moen, Jon; Chapin, F. Stuart; Bråthen, Kari Anne; Cabeza, Mar; Callaghan, Terry V.; van Oort, Bob; Dannevig, Halvor; et al. (Ecology and society, 2015)
Humans depend on services provided by ecosystems, and how services are affected by climate change is increasingly studied. Few studies, however, address changes likely to affect services from seminatural ecosystems. We analyzed ecosystem goods and services in natural and seminatural systems, specifically how they are expected to change as a result of projected climate change during the 21st century. We selected terrestrial and freshwater systems in northernmost Europe, where climate is anticipated to change more than the global average, and identified likely changes in ecosystem services and their societal consequences. We did this by assembling experts from ecology, social science, and cultural geography in workshops, and we also performed a literature review. Results show that most ecosystem services are affected by multiple factors, often acting in opposite directions. Out of 14 services considered, 8 are expected to increase or remain relatively unchanged in supply, and 6 are expected to decrease. Although we do not predict collapse or disappearance of any of the investigated services, the effects of climate change in conjunction with potential economical and societal changes may exceed the adaptive capacity of societies. This may result in societal reorganization and changes in ways that ecosystems are used. Significant uncertainties and knowledge gaps in the forecast make specific conclusions about societal responses to safeguard human well-being questionable. Adapting to changes in ecosystem services will therefore require consideration of uncertainties and complexities in both social and ecological responses. The scenarios presented here provide a framework for future studies exploring such issues.